Do part-time administrative positions of teachers affect student achievements? Evidence from a randomly assigned classes quasi-experiment - Feng, Chen; Gao, Yue-Guang; Liu, An-Zhuo; Zhang, Yao (International journal of educational development, 2025)
Teachers are often responsible for both teaching and administration in primary and secondary schools, but the effects on student achievements have not received enough attention. This paper examines how teachers’ responsibilities for administrative tasks affect student achievements based on a randomly assigned classes quasi-experiment. The results find that part-time administrative positions lower student achievements by about 0.83 standard deviations, and these effects are more pronounced for higher level administrative positions. Moreover, we find that these effects may be seen mainly in the mathematical subjects, and male and local students are more sensitive to them. The main reason is that part-time administrative positions reduce teachers’ regular teaching activities and time to communicate with students. This paper not only contributes to the literature on teacher characteristics and student performance, but also provides insights into relevant teacher administration policies. •This paper examines how the teacher with an administrative position affects student achievements.•The results indicate that administrative part-time positions lower student achievements by about 8.3 points.•We find that these effects may be mainly in the mathematics subjects.•We suggest that these effects leave teachers without regular teaching activities and time to communicate with students.